Implicit theory of personality as a prerequisite for pedagogical intuitions development - Yulia M. Garipova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article is devoted to the study of pedagogical intuition, its interconnection with the ideas of man about intellect and personality. Pedagogical intuition is frequently used in teachers' work, but the concept of pedagogical intuition and ways of its development is not clear. At the same time, developed pedagogical intuition, as an ability of a teacher to make quick decisions in their professional activity, allows them to simplify and speed up the process of solving professional issues, which is especially important for modern Russian teachers. Due to the high level of bureaucratization of education and a large teaching load, teachers in Russia are very time-bounded in their work.The article suggests that pedagogical intuition can be developed through the development of other personal characteristics. This study examined the relationship of intuitive abilities on the one hand, and the implicit theories of the personality, its learning objectives - on the other. To confirm this thesis, 50 senior students of the pedagogical university of Naberezhnye Chelny were interviewed. Since the sample was not large, the author of this article does not deny the possible error in the results of the study. However, it should be noted that the sample of the study will be increased several times to confirm the results obtained.As a result of the study, significant results were obtained on two scales of the questionnaire of implicit theories and learning objectives by C. Dweck and the questionnaire of the intuitive style of S. Epstein.